PENGARUH PRODUK DOMESTIK BRUTO DAN INFLASITERHADAP INDEKS HARGA SAHAM GABUNGAN DI BURSAEFEK INDONESIA TAHUN 2002-2009 - Prasetyanto, Panji Kusuma (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2017)
This study aims to determine (1) Effect of Gross Domestic Product on Stock PriceIndex (IHSG) in Indonesia Stock Exchange (BEI) in 2002 to 2009, (2) Effect ofInflation on Stock Price Index (IHSG) in Indonesia Stock Exchange (BEI) in 2002-2009.The population in this study is the price index of all shares listed on the StockExchange (BEI) from 1 January 2002 until 31 December 2009. The samples in thisstudyusing saturation sampling or sample census. Data collection technique useddocumentation techniques. Analysis of the data in this study using four types of test,namely: (1) descriptive statistics, (2) the classical assumption, (3) a regression testand (4) test the hypothesis. This study using SPSS version 17.0 for data processing.The results showed that (1) the Gross Domestic Product significant positive effecton the t-count IHSG 10.793 and 0.000 significance, (2) Inflation had no significanteffect onIHSG by t-test 1.942 and 0.062 significance.